Analysis of the Internal Control System for Goods Inventory in Vocational High Schools: Analisis Sistem Pengendalian Internal Persediaan Barang di SMK - Rizqollatifah, Sakinah Alfi; Maryanti, Eny (Indonesian Journal of Law and Economics Review, 2022)
The times are growing as well as human habits in doing shopping to meet their needs every day, therefore the way of selling has also changed to be more sophisticated and easy and the products are more varied to meet the demands of customers. This study aims to determine whether the internal control of merchandise inventory contained in the Bussiness Center of SMKN 2 Buduran is in accordance with the 2013 COSO theory. This study uses qualitative methods, while for data collection using documentation, interviews, observations and checklists related to this research . The data analysis technique used to answer the problems in this study is descriptive analysis. The results of the study prove that the analysis of the internal control of merchandise inventory at the Bussiness Center at SMKN 2 Buduran is mostly in accordance with the five components of COSO 2013 namely the implementation of 58.90% with an indication that it is quite effective. Some parts of the five components that are mostly not in accordance with COSO 2013 are risk assessment, control activities.